The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/remav-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Determine the Impact of Energy Intensity on the Market Value of Residential Units on the Example of Selected Buildings in Szczecin

Abstract: Environmental requirements, constantly increasing energy prices as well as energy consumption by residential units and buildings have become an important factor in the decision-making processes in the real estate market. The preferences of residential unit buyers who recognize the problem of energy intensity and translate it into the transaction price have also been changing. However, amendments to the Act on real estate management and new European standards have imposed an obligation to include the certificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…was modified. The earlier results showed that the previous classification was too fragmented, which resulted in the small size of individual groups, and were eventually found useful in the analysis of heat consumption (Foryś et al, 2019). With the help of the factor analysis, buildings were consequently grouped into 5 subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…was modified. The earlier results showed that the previous classification was too fragmented, which resulted in the small size of individual groups, and were eventually found useful in the analysis of heat consumption (Foryś et al, 2019). With the help of the factor analysis, buildings were consequently grouped into 5 subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 presents the parameters of the multiple regression function taking into account the important attributes influencing the value of the property. The introduction of the time variable t significantly improved the quality of model matching (Foryś et al, 2019). Depending on the period, the introduced attributes explained the evolution of the unit price in 78%, 75% and 24%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists made attempts to study indirect factors influencing housing construction, particularly the level to which energy intensity impacts the market price of residential buildings (Foryś et al, 2020), how a woman's opinion influences the final decision whether or not to make a purchase on the real estate market (Źróbek et al, 2020); how the globalization processes and free trade agreement influence the housing construction market (Cariaga & El-Diraby, 2013). Political uncertainty has a particularly strong impact on the housing market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, calculation of energy use can be based on the data closer to the real state. This is a very important issue because the energy certificates affect the transaction prices on the retail market [41,42]. For these reasons, studies based on the measurements in real conditions are of special interest.…”
Section: Introductionmentioning
confidence: 99%